Identification and molecular characterization of tropical cyanobacteria of the genus Nostoc, Calothrix, Tolypothrix and Scytonema (Nostocales: Nostocaceae), with possible biotechnological potential (UNED Research Journal, 2017)
Cyanobacteria or “Blue-Green” algae comprise a diverse cluster of prokaryotic photoautotrophs that share a high morphological and molecular abundance. Biotechnological advances on nitrogen fixation, bioremediation, pharmaceutical and nutritional value have been developed. Traditional identification based on morphology has been the most common applied technique, but it may be inaccurate because of the phenotypic plasticity that those organisms present. For this reason, molecular techniques had become robust tools for taxonomic positioning of tropical cyanobacterial isolates, associated with morphology identification. This study focuses on the morphological identification and molecular characterization of cyanobacteria isolated in different tropical environments of Costa Rica, for biotechnological prospects. Strains were grown in BG0-11 media, photographed under light microscope and classified at genera level. Molecular identification was carried by PCR and sequencing using DNA-dependent RNA polymerase (rpoC1) and small-subunit ribosomal RNA (16S rRNA) gen primers. Subsequently, a phylogenetic positioning analysis was performed by MAFFTv.7 alignment and maximum likelihood by raxMLGUI. Based on phenotypic characteristics, four genera of Nostocales were identified: Calothrix sp., Tolypothrix sp., Scytonema sp. and Nostoc sp. Molecular analysis shows a taxonomic grouping that is consistent with the observed morphology, with the 16S rDNA gene yielding robust and stable results. The identified genera are known for their nitrogen fixation capability: Nostoc and Calothrix have been used in maintaining fertility and soil recovering studies. Nostoc is known for its nutritional properties and biofuel production; a characteristic shared by Tolypothrix as well. The last genera; Scytonema, it is known for its pharmacological properties. With the successful identification of cyanobacteria strains isolated from tropical environments, it is possible to continue the study of genes responsible for properties of biotechnological interest and to evaluate their potential, with future perspectives of application and biodiversity conservation.
Keywords: Cyanobacteria; 16S rRNA; rpoC1; characterization molecular; morphological identification; biotechnological potential